Sensitive Spectrophotometric Methods for the Determination of Gatifloxacin in Pharmaceuticals Using Bromate-Bromide, Methylene Blue and Rhodamine-B as Reagents - K. Basavaiah; U. R. Anil Kumar (E-Journal of Chemistry)
Two new simple, precise, rapid and extraction-free spectrophotometric methods are proposed for the determination of gatifloxacin(GTF) using bromate-bromide mixture and two dyes, methylene blue and rhodamine B, as reagents. Spectrophotometric methods entail the addition of a known excess of bromate-bromide mixture to GTF in hydrochloric acid medium followed by determination of residual bromine by reacting with a fixed amount of either methylene blue and measuring the absorbance at 665 nm (Method A) or rhodamine B and measuring the absorbance at 555 nm (Method B). Beer᾽s law is obeyed in the ranges, 0.5-5.0 and 0.2-1.5 μg mL-1 for method A and method B, respectively. The apparent molar absorptivities are calculated to be 5.6×104 and 9.6×104 L mol-1cm-1 for method A and method B, respectively, and the corresponding Sandell sensitivity values are 0.0071 and 0.0042 μg cm-2. The methods were successfully applied to the assay of GTF in pharmaceutical formulations with satisfactory results.